2020
DOI: 10.3390/ijgi9110641
|View full text |Cite
|
Sign up to set email alerts
|

Time-Series of Vegetation Indices (VNIR/SWIR) Derived from Sentinel-2 (A/B) to Assess Turgor Pressure in Kiwifruit

Abstract: For more than ten years, Central Chile has faced drought conditions, which impact crop production and quality, increasing food security risk. Under this scenario, implementing management practices that allow increasing water use efficiency is urgent. The study was carried out on kiwifruit trees, located in the O’Higgins region, Chile for season 2018–2019 and 2019–2020. We evaluate the time-series of nine vegetation indices in the VNIR and SWIR regions derived from Sentinel-2 (A/B) satellites to establish how m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…In the SWIR spectra, there is a second CH overtone band that arises in the band range between 1,110 and 1,130 nm and a first CH overtone band that arises in the band range between 1,645 and 1,670 nm. Our model also predicts the presence of OH in the wavelength region between 650 and 780 nm for the VIS/NIR spectra, matching the findings in Zhang et al (2012) and Jopia et al (2020). Similarly, the OH prediction at the 1,205 and 1,450 nm bands of the SWIR images matches the findings from Frizon et al (2015) and Yan et al (2021).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the SWIR spectra, there is a second CH overtone band that arises in the band range between 1,110 and 1,130 nm and a first CH overtone band that arises in the band range between 1,645 and 1,670 nm. Our model also predicts the presence of OH in the wavelength region between 650 and 780 nm for the VIS/NIR spectra, matching the findings in Zhang et al (2012) and Jopia et al (2020). Similarly, the OH prediction at the 1,205 and 1,450 nm bands of the SWIR images matches the findings from Frizon et al (2015) and Yan et al (2021).…”
Section: Discussionsupporting
confidence: 79%
“…The plant spectral data in the wavelength between 400 and 990 nm for the VIS/NIR spectra and between 920 and 1,970 nm for the SWIR are characterized by several peaks. In VIS/NIR the spectra, the wavelength between 442 and 665 nm indicates the water status (Jopia et al, 2020). Similarly, the wavelength at around 780 nm is the region that indicates the water absorption (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The 945 nm wavelength region had the highest covariance, i.e., the highest overall reflectance intensity, and this is the reason why the algorithm selected and sorted it in the first round. Regarding the spectral slices selected in the second and third rounds, with the range between 1,600 and 2,500 nm, i.e., in the shortwave infrared (SWIR) domain, it is well-known that the reflectance in this region of the spectrum is strongly correlated with vegetation water content (Jopia et al, 2020;Holzman et al, 2021). However, the second round (2,190 nm) showed a baseline additive-type trend profile that reveals, as the first round, possible effects derived from the remote sensing spectral measurement.…”
Section: Spectral Slicesmentioning
confidence: 99%
“…It is likely that low-dose applications of these supplements at the onset of a water deficit could also have a synergistic effect on stress defence systems. In this sense, Jopia et al (2020) showed that water deficit could decrease growth by reducing the water potential. Stomatal closure and reduced water flow lead to physiological and biochemical changes also through the production of reactive oxygen species (ROS).…”
mentioning
confidence: 99%